From demand forecasting to inventory ordering decisions for red blood cells through integrating machine learning, statistical modeling, and inventory optimization. Issue 1 (16th November 2021) - Li, Na; Arnold, Donald M.; Down, Douglas G.; Barty, Rebecca; Blake, John; Chiang, Fei; Courtney, Tom; Waito, Marianne; Trifunov, Rick; Heddle, Nancy M.
Abstract: Background: The demand and supply of blood are highly variable over time. Blood inventory management that relies heavily on experience‐based decisions may not be adaptive to real demand, leading to high operational costs, wastage, and shortages. Methods: We combined statistical modeling, machine learning, and optimization methods to develop a data‐driven demand forecasting and inventory management strategy for red blood cells (RBCs). We then used the strategy to inform daily blood orders. A secondary semi‐weekly (twice per week) ordering strategy was developed to handle the last‐mile split delivery problem for blood suppliers, characterized by multi‐deliveries to the same location multiple times during a short period of time. Both strategies were evaluated using the TRUST database including all patient data across four hospitals in Hamilton, Ontario. Results: We identified 227, 944 RBC transfusions for 40, 787 patients in Hamilton, Ontario from 2012 to 2018. The predicted daily demand from the hybrid demand forecasting model was not significantly different from the actual daily demand (paired t ‐test p ‐value = 0.163); however, the proposed daily ordering quantity from the model was significantly lower than the actual ordering quantity ( p ‐value <0.001). The proposed daily ordering strategy reduced inventory levels by 38.4% without risk of shortages, leading to an overall cost reduction of 43.0% (95% confidence interval [CI]: 42.3%, 43.7%) compared with the actual cost. The semi‐weekly ordering strategy reduced ordering frequency by 62.6% (95% CI: 61.5%, 63.7%). Conclusion: The proposed data‐driven ordering strategy combining demand forecasting and inventory optimization can achieve significant cost savings for healthcare systems and blood suppliers.